2020
DOI: 10.3390/molecules25235685
|View full text |Cite
|
Sign up to set email alerts
|

Promising Lead Compounds in the Development of Potential Clinical Drug Candidate for Drug-Resistant Tuberculosis

Abstract: According to WHO report, globally about 10 million active tuberculosis cases, resulting in about 1.6 million deaths, further aggravated by drug-resistant tuberculosis and/or comorbidities with HIV and diabetes are present. Incomplete therapeutic regimen, meager dosing, and the capability of the latent and/or active state tubercular bacilli to abide and do survive against contemporary first-line and second line antitubercular drugs escalate the prevalence of drug-resistant tuberculosis. As a better understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Although multiple sites can be targeted to functionalize 4hydroxycoumarin, position 3-substituted derivatives are subject of interest for pharmacological use. [14][15][16] The nucleophilic carbon in position 3 leads to the creation of a new carboncarbon bond, which is one of the main pillars of organic synthesis. Several synthetic techniques are employed to make a new carbon-carbon bond, however, the multicomponent reactions such as Mannich reaction is considered one of the most important high-atom economic carbon-carbon bond forming strategy to produce β-amino carbonyl compounds referred to as the Mannich base.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple sites can be targeted to functionalize 4hydroxycoumarin, position 3-substituted derivatives are subject of interest for pharmacological use. [14][15][16] The nucleophilic carbon in position 3 leads to the creation of a new carboncarbon bond, which is one of the main pillars of organic synthesis. Several synthetic techniques are employed to make a new carbon-carbon bond, however, the multicomponent reactions such as Mannich reaction is considered one of the most important high-atom economic carbon-carbon bond forming strategy to produce β-amino carbonyl compounds referred to as the Mannich base.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds have been identified during the last few years with potential anti-tubular properties and are currently undergoing preclinical and clinical studies like, bedaquiline ( Antoci et al, 2021 ; Chakraborti et al, 2021 ; Patil & Jain, 2021 ; Deshkar & Shirure, 2022 ), PA-824 ( Lenaerts et al, 2005 ; Edwards & Field, 2022 ; Xu et al, 2022 ; Yan et al, 2022 ), and delamanid ( Skripconoka et al, 2013 ; Liu et al, 2018 ; Nasiri et al, 2022 ). Existing drugs have also been modified to repurpose them against TB and they include -riminophenazines ( Valinetz et al, 2020 ; Brunaugh et al, 2022 ), b-lactams ( Moon et al, 2018 ; Story-Roller & Lamichhane, 2018 ; Ur Rahman et al, 2018 ), and oxazolidinones ( Balasubramanian et al, 2014 ; Alghamdi et al, 2020 ; Margaryan et al, 2022 ; Ndukwe et al, 2022 ). These are examples of how in silico approaches have been successfully employed in retrieving promising lead compounds in preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have even proved that coumarin class of compounds interfere with the fatty‐acyl‐acyl carrier protein synthase (ACP) activity of the FadD32 enzyme, which is critical to Mycobacterium tuberculosis survival [23] . Coumarin derivatives are known to exhibit antitubercular properties by disrupting cytochrome synthesis, suppressing cell proliferation, activating macrophage, and inhibiting kinase activity [24,25] . Mangasuli et al., demonstrated that coumarin‐based compounds possessed strong binding affinity with MTB 4DQU enzymes [26] .…”
Section: Introductionmentioning
confidence: 99%
“…[23] Coumarin derivatives are known to exhibit antitubercular properties by disrupting cytochrome synthesis, suppressing cell proliferation, activating macrophage, and inhibiting kinase activity. [24,25] Mangasuli et al, demonstrated that coumarin-based compounds possessed strong binding affinity with MTB 4DQU enzymes. [26] These data clearly suggests that modification to the coumarin skeleton may lead to new anti-TB medicines with enhanced features, such as increased efficacy against both drug-resistant and drug-susceptible strains, lower toxicity, shorter therapy duration, and mycobactericidal capabilities.…”
Section: Introductionmentioning
confidence: 99%